«Indígena Always Has to Innovate»: Transformations of Ethnicity of the Otavalo Trade Diaspora - Sobczyk, Rita; Soriano Miras, Rosa (Revista Española de Antropología Americana, 2017)
The Kichwas from Otavalo (Ecuador) are one of the indigenous groups most affected by the global demand for the «culturally authentic» products. The commercial success of their handicrafts had a profound impact on reaffirmation of indigenous identity. This study analyzes the transformations of ethnicity of this population in the migratory context of Southern Spain. The results reveal the erosion of the transnational entrepreneurship which originally stimulated the migratory flows of Otavalos. The reorientation of the occupational strategy and their settlement in the receiving context influence the need to rethink the present meaning of ethnic dimension of identity.
Keywords: Ethnicity; Kichwa Otavalo; transnationalism; Spain.